Wheat productivity and profitability under different sowing window and irrigation scheduling based on weather model and spatial data in north Western Himalayas - PAREEK, BHEEM; RANA, RANBIR SINGH; RANA, NAVJOT; MANUJA, SANDEEP; KUMAR, NITESH; PAREEK, N.K. (Journal of Soil and Water Conservation, 2024)
Water is considered as one of the most crucial inputs for agricultural production. The decreasing water resource for agriculture production system in the face of climate change necessitates the use of real time weather data for reducing the water footprints of the crop. A field experiment entitled “Effect of dates of sowing and irrigation scheduling on wheat productivity and profitability in North Western Himalayas” was conducted during Rabi season 2018-19 and 2019-20 at the experimental research farm of department of Agronomy, CSK HPKV, Palampur, Himachal Pradesh. The experiment comprising of three dates of sowing (25th October, 20th November & 10th December) and five irrigation treatments viz. Rainfed conditions (I1), two irrigations (I2), three irrigations (I3), Irrigation scheduling based on Penman Monteith modified (I4), Irrigation scheduling based on spatial reference ET of grid (I5) was laid out in Split Plot Design with three replications. The study findings revealed that the growth parameters viz., plant height, LAI and dry matter recorded significantly higher when crop sown on 25th October with three irrigations (I3) during both the years. The sowing window of 25th October observed to be the best among the dates of sowing for yield parameters during both the years. However, irrigation schedule based on Penman Monteith modified proved to be the best irrigation treatment being statistically at par with I2 and I3 irrigations schedules during 2018-19, whereas, I3 gave the highest yield in three irrigation schedules during 2019-20. Similarly, the yield parameters reflected in significantly higher yield in I4 irrigation (4432 kg ha-1) being at par with I3 irrigations (4140 kg ha-1) and I2 (3922 kg ha-1) compared to I5 (3812 kg ha-1) and I1 (3111 kg ha-1) irrigations in 2018-19. The yield parameters reflected in significantly higher yield in I3 irrigation (4109 kg ha-1) compared to I2 irrigations (3916 kg ha-1), I4 (3905 kg ha-1), I5 (3798 kg ha-1) and I1 (3441 kg ha-1) irrigations in 2019-20. The highest benefit cost ratio (B:C) was observed for 25th October sowing (2.33 and 2.35) with I4 irrigation treatment (2.04 and 2.12) during both years, respectively.